Fungal Pathogens Associated with Strawberry Crown Rot Disease in China - Yanting Zhang; Hong Yu; Meihua Hu; Jianyan Wu; Chuanqing Zhang (Journal of Fungi, 2022)
Strawberry crown rot (SCR) is a serious disease that is generally referred to as seedling anthracnose due to its association with Colletotrichum spp. Presently, SCR is the main cause of death of strawberry seedlings. However, management strategies, including fungicides targeting Colletotrichum spp., have failed to obtain satisfactory results. Therefore, identifying the exact pathogen species causing SCR could guide its management. A total of 287 isolates were obtained from SCR-diseased plants. Based on the culture, morphology, and phylogenetic characteristics, the above 287 fungal isolates of SCR pathogens were identified as 12 different species, including Colletotrichum siamense, C. fructicola, Fusarium oxysporum, F. commune, F. equiseti, F. solani, F. tricinctum, Epicoccum sorghinum, Stemphylium lycopersici, Clonostachys rosea, Phoma herbarum, and Curvularia trifolii. Pathogenicity results showed that most isolates were pathogenic to strawberry seedlings and exhibited different degrees of virulence. In severe cases, poor growth on the ground, yellowing of the leaves, and even death of seedlings occurred. In mild cases, only black disease spots appeared on the stems of the strawberry seedlings, and a few withered leaves became necrotic. The inoculation experiments showed that the most virulent species were C. siamense and F. oxysporum, followed by F. equiseti, P. herbarum, Cl. rosea, S. lycopersici, and C. fructicola, which had disease incidences above 50%. E. sorghinum, S. lycopersici, Cl. rosea, P. herbarum and Cu. trifolii were reported to cause SCR for the first time herein. In conclusion, SCR is a sophisticated disease caused by a diversity of pathogenic fungi. This work provides new valuable data about the diversity and pathogenicity of SCR pathogens, which will help in formulating effective strategies to better control of the SCR disease.